Structure and Physical Properties of Ceramic Materials Based on ZrO2-Sc2O3 for SOFC Electrolytic Membranes Obtained from Powders of Melted Solid Solutions with a Similar Composition - Dmitrii Agarkov; Mikhail Borik; Ekaterina Buzaeva; Galina Korableva; Alexey Kulebyakin; Irina Kuritsyna; Nataliya Larina; Vladimir Kyashkin; Elena Lomonova; Filipp Milovich; Valentina Myzina; Polina Ryabochkina; et al. (Membranes, 2023)
This paper presents the results of studying the phase composition, luminescent characteristics, and ionic conductivity of ceramic scandium-stabilized solid solutions of zirconium dioxide containing 9 and 10 mol% Sc2O3. Ceramic samples were prepared by sintering powders obtained by grinding melted solid solutions of the same composition. A comparative analysis of the obtained data with similar characteristics of single crystals has been carried out. Differences in the phase composition of ceramics and initial single crystals were found. The effect of the structure and properties of grain boundaries on the ionic conductivity of ceramic samples is discussed. It is shown that the differences in the ionic conductivity of ceramic samples and crystals are mainly due to changes in the structure and phase composition.